Craving freedom, we become slaves - Abd Razak, Dzulkifli (2009)
OF late, US President Barack Obama has voiced what is on everyone's mind — the "perils" of the Internet, especially the social networking, that is now becoming trendy and popular among all ages, rightly or wrongly. In what he called "the YouTube age," he cautioned youngsters "to be careful about what you post on Facebook" (assuming this is just an example), because it could come to haunt them later. This advice follows a recent study which reportedly suggests that employers in the United States are increasingly turning to such sites to conduct background checks on job applicants.